Formulation and Evaluation of Vanishing Cream Incorporating Moringa Oil - Ahmed Aboshrida; Mehad Zoto (AlQalam Journal of Medical and Applied Sciences, 2026)
Herbal cream offers several advantages over other synthetic creams. This study aimed to formulate and evaluate a vanishing cream incorporating Moringa Oleifera seed oil at various concentrations. The research specifically explored the feasibility of using natural beeswax as a substitute for the commonly used synthetic structuring agent, stearic acid. Eight formulations were developed across four concentration levels (High, Medium-1, Medium-2, and Low water content). The oil-in-water (O/W) emulsions were prepared by melting an oil phase (structuring agent, lanolin, cetyl alcohol, and Moringa oil) and blending it with an aqueous phase (water, KOH, and propylene glycol) at 70–75°C. The products underwent comprehensive quality control testing, including sensory evaluation, skin sensitivity, absorption time, washability, and pH stability. Our findings indicated that Moringa oil successfully incorporated into both stearic acid and beeswax cream bases without stability issues or air bubbles. Formulations with high water content ( 85%) exhibited excellent spread ability and rapid absorption (under 1 minute), whereas lower water concentrations resulted in a greasier skin feel. Stearic acid formulations remained skin-compatible (pH 5.5–7.5), while beeswax formulations showed higher alkalinity (pH 8.0–8.8). All formulations were non-irritant in skin sensitivity tests. So, Moringa oil is a highly suitable candidate for vanishing creams, providing moisturizing and antioxidant benefits while maintaining physical stability. While beeswax is a viable natural alternative, stearic acid remains superior for maintaining optimal pH and the characteristic "vanishing" effect.